2017
DOI: 10.1080/00222895.2017.1408557
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Perceptual-Motor Behavior Across the Expert Athlete to Disabled Patient Skill Continuum can Advance Theory and Practical Application

Abstract: A framework is presented of how theoretical predictions can be tested across the expert athlete to disabled patient skill continuum. Common-coding theory is used as the exemplar to discuss sensory and motor system contributions to perceptual-motor behavior. Behavioral and neural studies investigating expert athletes and patients recovering from cerebral stroke are reviewed. They provide evidence of bi-directional contributions of visual and motor systems to perceptual-motor behavior. Majority of this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Evidence suggests that robotic guided movements, in addition to typical motor areas, activate also deep neural centers such as the insula and the amygdala that are involved in movement memory and motivation to the movement and play a key role in inducing sensory processes related to the internal representation of the movements ( 68 ). Therefore, the simultaneous activation of sensory and motor systems could facilitate perceptual–motor skill learning and transfer ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that robotic guided movements, in addition to typical motor areas, activate also deep neural centers such as the insula and the amygdala that are involved in movement memory and motivation to the movement and play a key role in inducing sensory processes related to the internal representation of the movements ( 68 ). Therefore, the simultaneous activation of sensory and motor systems could facilitate perceptual–motor skill learning and transfer ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that some skilled subjects had greater dexterity of the untrained hand, with less error and faster movement together with activated structural reorganisation compared with unskilled subjects 58. Athletes may use this pattern with a continuous training modality to learn new skills and recover from injuries 59. Although MTr has only been used as a supplementary tool to compare skill levels between skilled and unskilled subjects,26 better methods of improving motor function are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies that have investigated visual and motor expertise (or experience) contributions to anticipation in sport have measured visual-perceptual anticipation, which involves a nonmotor prediction. In addition, the majority of studies have focused upon performance, rather than learning and transfer (Müller et al, 2018). In relation to performance, seminal studies were conducted by Abernethy and colleagues.…”
Section: Evidence Of Visual and Motor Contributions To Anticipationmentioning
confidence: 99%